Biochar de residuos de caña de azúcar: dosis y efectos en el cultivo de maíz (zea mays l.) - Moscoso Erraez, Jose Mauricio (Machala : Universidad Técnica de Machala, 2022)
Corn is one of the most important cereals worldwide, ranking first in production and third in terms of area covered, after wheat and rice. This crop has an enormous genetic richness that man has been creating over the years. In Ecuador, it is widely used in human and animal feed for the manufacture of animal feed. According to the volume of production, it is grown mainly in Los Ríos, Manabí, Guayas and Loja and to a lesser extent in other provinces to take advantage of the rains. Despite being very important, production does not cover the national need, so a significant amount is imported to satisfy the country. The main objective of this research was to determine the best dose of biochar and the effect it causes when applied to corn plants from the initial stage until harvest. It was developed in the experimental area of the Santa Inés farm, belonging to the Faculty of Agricultural Sciences of the Technical University of Machala, located at km 5.5 of the Machala-Pasaje road. Two varieties were planted: Hercules and ADV 9735 and four treatments were used with a control: T1 and T2 (2 and 4 g of sugarcane residue biochar respectively) and T3 and T4 (2 and 4 g of corn taraya residue). For the development of the research, 20 beds of 7 x 2.10 m separated by 0.80 m and with an aisle of 1 m were constructed, each bed was divided in two at 0.50 m to separate the biochar depending on the origin, in addition, for a better development, sprinkler irrigation was installed in the experimental area. The variables evaluated were: plant height, ear length, ear diameter, ear weight, ear diameter, ear diameter, rachis weight, rachis diameter, ear row arrangement, ear cover and ear damage. The data obtained were processed in the IBM SPSS STATICS 22 software where inter-subject effects tests were carried out to determine the significance between groups. The treatments used showed significant differences, for the variable Arrangement of rows in the ear, variety 2 presented irregularly with 2.01 and with the application of 2 g doses of corn residue biochar, the variable ear damage was obtained less damage in variety 1 with 0.79 and with corn residue biochar, for the variable length of the ear, the best result was obtained with 13. 21 cm with variety 1 Hercules and with the application of 4 g of sugarcane biochar doses, for variety 2 ADV 9735 and with the application of 2 g of sugarcane residues, better results were obtained for the variables, ear weight with 75.26 grams, ear diameter with 36.62 mm, ear weight with 13.18 grams, ear diameter with 23.31 mm and rachis diameter with 14.14 mm. These results show that sugarcane residue biochar influences some of the agronomic characteristics of the crop with relatively small doses.
El maíz es uno de los cereales más importantes a nivel mundial, ocupa el primer lugar en producción y tercero en relación con el área cubierta, después del trigo y arroz. Este cultivo posee una enorme riqueza genética que el hombre ha ido creando con el pasar de los años. En Ecuador es muy utilizado en la alimentación humana y animal para la fabricación de balanceados. Según el volumen de producción se cultiva principalmente en Los Ríos, Manabí, Guayas y Loja y en menor parte en otras provincias sembrado para aprovechar las lluvias. Pese a ser muy importante, la producción no cubre la necesidad nacional, por lo que se importan una significativa cantidad para satisfacer al país. El objetivo principal de esta investigación fue determinar la mejor dosis de biochar y el efecto que causa al ser aplicado a plantas de maíz desde su etapa inicial hasta la cosecha. Se desarrolló en el área experimental de la granja Santa Inés, perteneciente a la Facultad de Ciencias Agropecuarias de la Universidad Técnica de Machala, ubicada en el km 5,5 de la vía Machala-Pasaje. Se sembraron dos variedades: Hércules y ADV 9735 y se emplearon cuatro tratamientos: T1 y T2 (2 y 4 g de biochar de residuos de caña de azúcar respectivamente) y T3 y T4 (2 y 4 g de residuos de taraya de maíz). Para el desarrollo de la investigación se construyó 20 camas de 7 x 2.10 m separadas entre sí por 0.80 m y con un pasillo de 1 m, cada cama fue dividida en dos a 0.50 m para separar el biochar dependiendo del origen, además para un mejor desarrollo de instaló en el área experimental riego por aspersión. Las variables evaluadas fueron: altura de la planta, longitud de la mazorca, diámetro de la mazorca, peso del marlo, diámetro del marlo, peso del raquis, diámetro del raquis, disposición de hileras de la mazorca, cobertura de la mazorca y daños a la mazorca. Con los datos obtenidos se procesaron en el software IBM SPSS STATICS 22 donde se realizó pruebas de efectos inter-sujetos para conocer la significancia entre grupos. Los tratamientos empleados mostraron diferencias significativas, para la variable Disposición de hileras en la mazorca la variedad 2 presentó de forma irregular con 2.01 y con aplicación de 2 g dosis de de biochar de residuos maíz, variable daños de la mazorca se obtuvo menor daños en la variedad 1 con 0.79 y con biochar de residuos de maíz, para la variable largo de la mazorca se obtuvo mejor resultado con 13.21 cm con la variedad 1 Hércules y con aplicación de 4 g de dosis de biochar de caña, para la variedad dos ADV 9735 y con aplicación de 2 g de residuos de caña de azúcar se obtuvieron mejores resultados para las variables, peso de la mazorca con 75.26 gramos, diámetro de la mazorca con 36.62 mm, peso del marlo con 13.18 gramos, diámetro del marlo con 23.31 mm y diámetro del raquis con 14.14 mm. Con estos resultados se pone en evidencia que el biochar de residuos de caña de azúcar influye sobre algunas de las características agronómicas del cultivo y con dosis relativamente pequeñas.
Keywords: BIOCHAR; DOSIS; RENDIMIENTO; MAÍZ